Resistant starch, chronic kidney disease, and the gut microbiome: A mini‐review - Jiayue Guo; Amy Szacilo; Lingyan Kong (Food Frontiers)
Abstract The kidneys play a vital role in maintaining various homeostatic functions, yet the prevalence of chronic kidney disease (CKD) has been increasing globally. The review discusses how resistant starch supplementation in CKD patients can shift the gut microbiota composition, promoting short‐chain fatty acid‐producing bacteria, especially butyrate producers, and reducing mucin‐degrading bacteria. This shift is posited to reduce inflammation and oxidative stress, thereby potentially alleviating CKD progression. It also highlights the complexity of establishing clear causal pathways due to the current limitations in testing techniques for gut microbiota, which often lack the resolution needed to establish clear causal mechanisms. Therefore, this review stresses the need for future research to address these gaps, refine testing methods, clarify the health implications of microbiota shifts, and consider individual metabolic differences and variations in gut microbiota.